Comparison between Laparoscopic Surgeries & Lichtenstein Repair for the Treatment of Inguinal Hernias (Journal of Recent Advances in Applied Sciences (pISSN 0970-1990), 2026)
Introduction: Inguinal hernia repair is one of the most performed surgeries worldwide. While Lichtenstein tension-free mesh repair remains the standard open technique, laparoscopic approaches such as TAPP and TEP are increasingly favored due to improved postoperative recovery and patient comfort.Aim & Objectives: To compare laparoscopic repair and Lichtenstein repair for the treatment of inguinal hernias with respect to operative outcomes, postoperative pain, complications, recovery parameters, patient satisfaction, and cost.Materials & Methods: This prospective comparative study included 100 patients with inguinal hernia, equally divided into laparoscopic (n=50) and Lichtenstein repair (n=50) groups. Outcomes assessed included operative time, complications, postoperative pain, hospital stay, return to work, patient satisfaction, and treatment cost. Statistical significance was set at p